Inventing Vietnam the United States and State Building, 1954-1968 - Carter, James M. 1968- (Cambridge University Press, 2008)
This book considers the Vietnam war in light of U.S. foreign policy in Vietnam, concluding that the war was a direct result of failed state-building efforts. This U.S. nation building project began in the mid-1950s with the ambitious goal of creating a new independent, democratic, modern state below the 17th parallel. No one involved imagined this effort would lead to a major and devastating war in less than a decade. Carter analyzes how the United States ended up fighting a large-scale war that wrecked the countryside, generated a flood of refugees, and brought about catastrophic economic distortions, results which actually further undermined the larger U.S. goal of building a viable state. Carter argues that, well before the Tet Offensive shocked the viewing public in late January, 1968, the campaign in southern Vietnam had completely failed and furthermore, the program contained the seeds of its own failure from the outset
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Geschichte 1954-1968; Außenpolitik; Politik; Vietnamkrieg; Vietnam War, 1961-1975 / United States; Nationenbildung; USA; United States / Foreign relations / Vietnam; Vietnam / Foreign relations / United States; United States / Foreign relations / 1945-1989; Vietnam / Politics and government / 1945-1975; Vietnam